2021
DOI: 10.1111/jcmm.16305
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐130a inhibits proliferation of vascular smooth muscle cells by suppressing autophagy via ATG2B

Abstract: A large number of arteriosclerosis obliterans (ASO) cases occur in the SouthEast Asia and Western Pacific regions. 1 ASO affects mainly the small-and medium-sized arteries of the lower limbs and is characterized by lipid and inflammatory cell accumulation within the intima of large arteries. 2 Endovascular surgery has a good curative effect on ASO; however, the vascular restenosis that results from neointimal hyperplasia remains a problem, leading to the failure of revascularization procedures. 3,4 Vascular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Substantial evidence suggests that autophagy gets involved in the regulation of VSMCs disorder [ 4 , 23 ]. We found that autophagy was activated in HG-stimulated VSMCs, shown as an increased LC3B-II/-I ratio and a decreased SQSTM1/p62 expression, which was abrogated by si-hsa_circRNA_0008028 ( Figure 2(g) ).…”
Section: Resultsmentioning
confidence: 99%
“…Substantial evidence suggests that autophagy gets involved in the regulation of VSMCs disorder [ 4 , 23 ]. We found that autophagy was activated in HG-stimulated VSMCs, shown as an increased LC3B-II/-I ratio and a decreased SQSTM1/p62 expression, which was abrogated by si-hsa_circRNA_0008028 ( Figure 2(g) ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have documented that miR-130a is highly expressed in the heart and plays an important role in the development of cardiovascular diseases [ 12 , 13 , 15 , 32 ]. MiR-130a has a protective effect on cardiovascular diseases, for instance, Feng et al found that miR-130a attenuated cardiac fibrosis after myocardial infarction through transforming growth factor (TGF)-β/Smad signaling by directly targeting TGF-β receptor 1 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of autophagy, the transformation of LC3-II is an important step of autophagosomes [ 18 ]. In this present study, overexpression of mTOR or knockdown of miR-199a-3p could significantly inhibit autophagy process by suppressing Beclin-1 and LC3II/I ratio (Figures 5(a) – 5(c) ).…”
Section: Discussionmentioning
confidence: 99%